Consensus-based energy management of multi-microgrid: An improved SoC-based power coordinated control method - Liu, Xinrui; Zhang, Mingchao; Xie, Xiangpeng; Zhao, Liang; Sun, Qiuye (Applied mathematics and computation, 2022)
•Power regulation cost of controllable unit is modeled to arrange adjustment order.•SoC is considered to reduce the number of switching times of MMG working mode.•Consistency algorithm based on the load rate accelerates convergence speed of SoC.•Power allocation based on consensus algorithm reduces MMG power regulation cost. The direct current(DC) multi-microgrid(MMG) with island operation mode is a system formed by interconnecting DC multiple microgrids, which is more complicated than a single microgrid. First of all, this paper proposes the modeling method of the power regulation cost for each controllable unit to guide their power regulation order, which reduces the power regulation cost. Second, the hierarchical control strategy is proposed. The top-level control allocates power through the consensus algorithm to accelerate the convergence rate of the state of charge(SoC) of energy storage batteries(ESBs). The convergence of SoC reduces the switching times of working mode of MMG system caused by the deviation of SoC from the normal working range, which further reduces the cost of power regulation. The bottom-level control performs constant power control on each controllable unit according to the load rate of ESB obtained by top-level control. Furthermore, the correction scheme of measured SoC value is proposed according to its predicted value when the measured SoC value of ESB is inaccurate, which ensures the stability of MMG system. Finally, the example simulation shows that the consensus algorithm can effectively solve the real-time power distribution problem of MMG.